Uji Aktivitas Penghambatan Enzim Alfaglukosidase Pada Beberapa Tanaman Suku Euphorbiaceae - Elya, Berna; Katrin, Katrin; Bangun, Anastasia (UI Scholars Hub, 2012)
Diabetes mellitus (types 1 and 2) is recognized as a serious global health problem that characterized by hyperglycemia. Type 2 diabetes is more common in diabetic populations. In type 2 diabetes mellitus, inhibition of α-glucosidase is a useful treatment to delay the absorption of glucose after meals. Avoiding the adverse effects of current agents, it is still necessary to search alternative for better options. Plants have been a rich source of α-glucosidase inhibitors. In this research, screenings based on chemotaxonomic approach to determine the class of chemical constituents and to know α-glucosidase inhibiting activity of some plants from Euphorbiaceae. The simplisia powder was extracted using ethanol 80% by reflux. Measurement of inhibitory activity of α-glucosidase performed using a spectrophotometer UV-VIS. In vitro assays of α-glucosidase activity showed 14 extracts had IC50 values of between 2.34 µg/mL and 64.78 µg/mL, which were lower than that of acarbose (117.20 µg/mL). Leaves extract from Antidesma celebicum had the highest α-glucosidase inhibiting activity with an IC50 of 2.34 µg/mL. The results of phytochemical screening in 15 extracts generally contain glycosides, terpenoids/ sterols, tannins, saponins and alkaloids.